Comparative genomic analysis of clinical Acinetobacter nosocomialis isolates from Terengganu, Malaysia led to the discovery of a novel tetracycline-resistant plasmid. (December 2022) - Mohd Rani, Farahiyah; Lean, Soo Sum; A． Rahman, Nor Iza; Ismail, Salwani; Alattraqchi, Ahmed Ghazi; Amonov, Malik; Cleary, David W.; Clarke, Stuart C.; Yeo, Chew Chieng
HIGHLIGHTS: The genome sequence of four Acinetobacter nosocomialis clinical isolates is reported Three tetracycline-resistant isolates were closely related and harboured two plasmids The tetA(39) resistance gene is in a mobile p dif module in a Rep3 plasmid, pAC13-1 pAC13-2 is a cryptic PriCT-1 plasmid of a new Acinetobacter plasmid group, GR60 Both plasmids harboured mobilisation/transfer-related genes ABSTRACT: Objectives: To analyse the genome sequences of four archival Acinetobacter nosocomialis clinical isolates (designated AC13, AC15, AC21 and AC25) obtained from Terengganu, Malaysia in 2011 to determine their genetic relatedness and basis of antimicrobial resistance. Methods: Antimicrobial susceptibility profiles of the A. nosocomialis isolates were determined by disk diffusion. Genome sequencing was performed using the Illumina NextSeq platform. Results: The four A. nosocomialis isolates were cefotaxime resistant whereas three isolates (namely, AC13, AC15 and AC25) were tetracycline resistant. The carriage of the bla ADC-255 -encoded cephalosporinase gene is likely responsible for cefotaxime resistance in all four isolates. Phylogenetic analysis indicated that the three tetracycline-resistant isolates were closely related, with an average nucleotide identity of 99.9%, suggestive of nosocomial spread, whereas AC21 had an average nucleotide identity of 97.9% when compared to these three isolates. The tetracycline-resistant isolates harboured two plasmids: a 13476 bp Rep3-family plasmid of the GR17 group designated pAC13-1, which encodes the tetA(39) tetracycline-resistance gene, and pAC13-2, a 4872 bp cryptic PriCT-1-family plasmid of a new Acinetobacter plasmid group, GR60. The tetA(39) gene was in a 2 001 bp fragment flanked by XerC/XerD recombination sites characteristic of a mobile p dif module. Both plasmids also harboured mobilisation/transfer-related genes. Conclusions: Genome sequencing of A. nosocomialis isolates led to the discovery of two novel plasmids, one of which encodes the tetA(39) tetracycline-resistant gene in a mobile p dif module. The high degree of genetic relatedness among the three tetracycline-resistant A. nosocomialis isolates is indicative of nosocomial transmission.